Peran Komisi Pengawas Persaingan Usaha Untuk Mencegah Praktik Monopoli di Indonesia - Muttaqin, Muttaqin; Ratnawati, Elfrida (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
In general, the existence of government affects the economy at various levels. There are governments that rigidly or aggressively control the economy, and governments that limit themselves to supporting the economy. The purpose of this research is to find out the law against monopolistic behavior and/or unfair business competition. The methodology used is normative juridical, namely qualitative. The method used is qualitative with legal sources in the form of books, academic journals, academic opinions, and legal cases using secondary data. The results of the research show that the Commission for the Supervision of Business Competition is limited to examining all forms of agreements and acts against the law in Antimonopoly. Law, then carry out administrative actions, provide advice, and give consideration. This conclusion can be reached based on the information provided earlier. In addition, the Commission for the Supervision of Business Competition is tasked with enforcing the law and providing monthly reports on its actions.